MOLECULAR AND PHYLOGENETIC STUDY OF BACTERIA RESISTANT TO COAL FLY ASH - JABEEN , SITARA; M. P. SINHA (The Bioscan, 2013)
The assessment of the bacteria in coal fly ash has been a critical issue with respect to its enormous production and utilization purpose. 16S rDNA based fingerprints revealed the resistant bacteria to coal fly ash and the molecular analog was studied. The bacteria observed were Aeromonas punctata, Bacillus cereus, Bacillus probio 32 and Kocuria. The consensus sequences along with the significant alignment of the bacteria were revealed in turn helping in the formulation of their unrooted phylogenetic tree.